Dermatological manifestations during COVID-19 pandemic – Case series from Nepal - Shrestha, Rushma; Parajuli, Niraj; Amatya, Amit (Journal of General Practice and Emergency Medicine of Nepal, 2021)
ARS CoV-2 infection primarily targets the respiratory system, but other organs, including skin can also be affected with varied manifestations. The most common dermatological findings of COVID-19 include urticarial, maculopapular rash, papulovesicular exanthema, chilblain-like acral pattern, livedoreticularis-like pattern and purpuric “vasculitic” pattern. Here, we present a case series with skin findings in COVID-19 from Nepal